Drafting of the Project of Canons About Catholic Universities by the Pontifical Commission for the Revision of the Code of Canon Law (1968-1977) - Borowy, Rafał; Gosiewski , Radosław (Prawo Kanoniczne, 2024)
The renewal of church life in the 20th century, which culminated in the Second Vatican Council, in a some way forced the need to codify the norms about Catholic universities, which at the beginning of the second half of this century had not been comprehensively regulated in canon law. The task of drafting the canons of the Code was entrusted to the Pontifical Commission for the Revision of the Code of Canon Law. In the years 1968-1977, the Commission developed the first draft of canons about Catholic universities. This study presents in detail the process of preparing this project for sending it for consultation to the universal Church.